Coronary artery aneurysm in kawasaki disease - Achala Donuru; Maansi Parekh; Vinay V. R Kandula; Sharon Gould (Wolters Kluwer Medknow Publications, 2020)
A 3-year-old male presents to the emergency department with chief complaints of fever and vomiting. He had a positive rapid streptococcus throat test with cervical lymphadenopathy. The patient was started on antibiotics. On examination, there was diffuse erythematous macular rash on the chest. Laboratory tests revealed elevated white cell count and C-reactive protein. Electrocardiogram was notable for prolonged PR interval indicating 1st degree atrioventricular block. Echocardiogram revealed ectasia of the right coronary artery (RCA). A presumptive diagnosis of Kawasaki disease was made and the patient was started on high-dose aspirin and intravenous immunoglobulins. Cardiac computed tomography angiography (CTA) showed an aneurysm of the proximal RCA measuring up to 7.4 mm. The RCA immediately proximal to the aneurysm measured 3 mm in diameter. The Z score was 13.4. Oblique coronal image from cardiac CTA and volume rendered images demonstrated an aneurysm of the proximal RCA. The patient improved with treatment.